Syndicalisme et corporatisme dans l’Égypte contemporaine, Entre histoire sociale et sociologie politique - Elisabeth Longuenesse (Revue des Mondes Musulmans et de la Méditerranée)
The Nasser era saw the development of a number of professional organizations for occupational groups defined by specialized skills and university degrees, and mobilized for the national development project. A favorite object of study for political scientists, these "professional unions" are sometimes regarded as distant heirs of Ottoman guilds.The study focuses on the examination of theoretical interpretations, based on models with universalizing ambitions, and aims at demonstrating the value of an approach inspired by social history and Sewell's work, which takes into account the persistence of idioms through historical discontinuities.